Performance of Custom-Fit versus Fixed-Format Hearing Aids for Precipitously Sloping High-Frequency Hearing Loss - Walden, Therese C.; Walden, Brian E.; Cord, Mary T. (Journal of the American Academy of Audiology, 2002)
This study compared the real-ear response provided by custom-fit hearing aids to the closest matching fixed-format disposable hearing aids in patients with precipitous high-frequency hearing loss. Laboratory and field measures of aided performance were obtained to compare patient performance with the custom-fit and fixed-format hearing aids. In addition, coupler versus real-ear response differences were compared for the two hearing aid types. The results revealed that relatively close approximations to the real-ear aided responses of the custom-fit instruments were possible for most participants using seven fixed acoustic formats. No significant differences in mean performance between the two instrument types were observed for aided speech recognition or field ratings of aided performance, although mean patient satisfaction was lower for the disposable hearing aids. The real-ear to coupler difference was greater for the disposable hearing aid than for the custom-fit instruments, presumably owing to its deeper insertion into the ear canal.
Keywords: Benefit; custom fit; disposable; hearing aids; real-ear aided response; satisfaction; speech recognition